Teacher's Strategis To Overcome The Students Mental Block In Speaking English - Laila Nurizmi; Ahmad khatami; Sulastri Sulastri; Lalu deni Kurniawan; Selamet Riadi Jaelani (LPPM Politeknik Pratama, 2023)
This study was to find teacher’s strategies to overcome the student mental block in speaking English. The participants of this article were tutor at Linkage, Bale Beleq, Best One and FLC. The data were collected by using questioner and interview from 5 tutor at course. The result is to find various strategies to slove the mental block student such as student center learning (SCL), pair teaching, gaming, and limited practice. the result also to implementing a combination of supportive teaching strategies and creating an encouraging classroom environment, so teachers can help the students to overcome their mental blocks and become confident and proficient English speakers. the good implementation of these strategies can make the students be better prepared to in an interconnected society that requires excellent communication skills by successefully implementing these tactics.